2011
DOI: 10.1021/ja1102844
|View full text |Cite
|
Sign up to set email alerts
|

Chiral 1,2,3-Triazoliums as New Cationic Organic Catalysts with Anion-Recognition Ability: Application to Asymmetric Alkylation of Oxindoles

Abstract: Chiral 1,2,3-triazoliums have been designed, and the rational structural modification based on their unique anion-binding abilities has led to the establishment of the highly enantioselective alkylation of 3-substituted oxindoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(79 citation statements)
references
References 36 publications
1
72
0
6
Order By: Relevance
“…Ooi and co-workers have reported the development of chiral 1,2,3-triazolium salts (such as 152ÁBr) that function as cationic organocatalysts with anion recognition abilities. 84 The increased CH-acidity of the triazolium cation versus the simple 1,4-disubstituted 1,2,3-triazole unit means an increased anion binding capacity. X-ray crystallography of 152ÁCl showed that the combination of electrostatic interactions, CHÁ Á Áanion hydrogen bonding and a suitably positioned amide NHÁ Á Áanion hydrogen bond forms a structured and tightly bound ion pair.…”
Section: Catalysismentioning
confidence: 99%
“…Ooi and co-workers have reported the development of chiral 1,2,3-triazolium salts (such as 152ÁBr) that function as cationic organocatalysts with anion recognition abilities. 84 The increased CH-acidity of the triazolium cation versus the simple 1,4-disubstituted 1,2,3-triazole unit means an increased anion binding capacity. X-ray crystallography of 152ÁCl showed that the combination of electrostatic interactions, CHÁ Á Áanion hydrogen bonding and a suitably positioned amide NHÁ Á Áanion hydrogen bond forms a structured and tightly bound ion pair.…”
Section: Catalysismentioning
confidence: 99%
“…18 The catalyst ability of 22 was initially examined in asymmetric phase-transfer alkylation of oxindole derivative 24a. 13 Although newly-designed catalyst 22a…”
Section: Amino Acid-derived Catalystsmentioning
confidence: 99%
“…Die Optimierung der Katalysatorstruktur und des Lçsungs-mittels führte zu nahezu quantitativen Ausbeuten und Enantiomerenüberschüssen bis 97 %. [226] 6.1.2. Chirale Anionen als Katalysatoren in der organischen Chemie…”
Section: Anionenkanäleunclassified